Estrategias Metodológicas en el proceso de enseñanza aprendizaje de los niños de 4años del CDI San Nicolás del Cantón Paltas 2023-2024 - Nole Nole, Cindy Yelena (2024)
This curricular integration paper’s general objective was to analyse the methodological strategies and their influence on the teaching-learning process in 4-year-old children from the CDI ‘San Nicolás’ school, Paltas canton 2023- 2024. This research addresses various difficulties within the teaching-learning process such as complications understanding activities, communication, attention and behaviour; which often lead to the student’s social isolation. These difficulties may be negatively influenced by the methodological strategies employed by teachers, which suggests the need to review and adapt pedagogical methodologies to improve the integral development of students. To this end, relevant information was summarised and analysed using a descriptive, non-experimental, cross-sectional, qualitative methodology, which enabled data collection at a specific time. The sample population comprised 1 teacher and 7 kindergarten-2 children. For data collection, we used an interview form and an observation guide. The theoretical perspective was developed from an academic documentation review, including articles and undergraduate theses available in repositories and digital scientific journals. The results achieved evidence that the teacher certainly uses an unlimited variety of methodological strategies in the teaching-learning process; however, a deficient motivation is observed in the children regarding classwork. The research findings provided us with the tools to emphasise the need for a well-structured methodological approach, suggesting that a combination of appropriate pedagogical techniques can create a more effective and balanced educational environment, thus promoting a holistic development of children. Key words: Dimensions of learning, Children’s workshops, Puppets, Children's stories, Children’s games.